The role of gene polymorphisms in individually changing of the lipid profile among patients with coronary artery disease under the influence of the statin therapy - Fushtey, I. M.; Sid, E. V.; Litvinenko, V. V. (Modern medical technology, 2019)
Ischemic heart disease is one of the urgent problems in modern cardiology, which is associated with a wide spread of disability and mortality mainly among young and employable aged people. The therapeutic drugs effect is individual and depends on the genetic characteristics of the patient. The aim of the study. Analysis of modern literature sources related to the role of gene polymorphisms in individual lipid profile changing among patients with coronary artery disease under the influence of the statin therapy. Literature review. Pharmacotherapy while ischemic heart disease (IHD) provides for mandatory preventive services aimed at the eliminating of modifying risk factors of coronary heart disease. One of the most important indicators of successful treatment of patients with IHD is a lipid metabolism state, that is why treatment can’t be imagined without the inclusion of statins in therapeutic schemes of dyslipidemia correction. The current understanding of the statins effectiveness is based on the knowledge of molecular mechanisms underlying the pharmacokinetics and pharmacodynamics processes. In clinical practice, while taking statins with absolute compliance of patients and elimination of all modifying factors, lipid metabolism parameters are not always normalized, this indicates characteristics of the patients’ genetic. Of particular importance is the effect of genotype on pharmacotherapy using protein transporters, carriers of endogenous compounds or xenobiotics through biological membranes assisted by passive or active mechanisms. Single-nucleotide polymorphisms (SNPs) of transport proteins can change the absorption and excretion degree of drugs and their metabolites. Polypeptides of organic anions membrane transporters that regulate cell uptake of certain endogenous substances and drugs are encoded by SLCO genes. One of the main absorption protein transporters is OATP1B1. It is established that the effects of some SLCO1B1 SNPs on transport function are substrate dependent, and the most studied among them are с.521Т>С and с.388А>G. The c.521Т>C and с.388А>G polymorohisms c.521T>C". Но c.521T>C are in an intermittent contact with each other, and despite this they exist in a variety of SLCO1B1-haplotypes. The c.388А-521Т haplotypes known as *1A ones, c.388G-521Т as *1B, c. 388А-521С as *5 and c.388G-521С as *15. One of the first studies showed that *5 and *15 haplotypes were associated with a decrease in the absorption of statins. In further studies of c.521C allele it was found a related increase of the statins concentration in human plasma, which leads to the progression of undesirable reactions such as myalgia, myopathy, and even rhabdomyolysis, asymptomatic increase transaminase activity and abdominal pain. The study of SLCO1B1 pharmacogenetics found that dysfunction of the protein-transporter leads to reduced absorption by the liver cells, the increasing of plasma concentrations and the change in the body's response to stationery. Conclusion. Analysis of the literature indicates that the therapeutic effect of statins in combination with genetic polymorphisms may have an individual effect on the pharmacokinetics of these drugs. To study the influence of SLCO1B1 c.521Т>С gene polymorphism there are needed the further researches in populations with IHD. A more detailed study of this polymorphism from the perspective of personalized therapy will allow developing individual approaches to the appointment of statins.